It's Not Just the Prices: Time-Driven Activity-Based Costing for Initiation of Veno-Venous Extracorporeal Membrane Oxygenation at Three International Sites—A Case Review. (1st June 2022) - Nurok, Michael; Pellegrino, Vin; Pineton de Chambrun, Marc; Warsh, Jonathan; Young, Meredith; Dong, Erik; Parrish, Neil; Shehab, Syed; Combes, Alain; Kaplan, Robert S.
Abstract : The United States spends more for intensive care units (ICUs) than do other high-income countries. We used time-driven activity-based costing (TDABC) to analyze ICU costs for initiation of veno-venous extracorporeal membrane oxygenation (VV ECMO) for respiratory failure to estimate how much of the higher ICU costs at 1 US site can be attributed to the higher prices paid to ICU personnel, and how much is caused by the US site's use of a higher cost staffing model. We accompanied our TDABC approach with narrative review of the ECMO programs, at Cedars-Sinai (Los Angeles), Hôpital Pitié-Salpêtrière (Paris), and The Alfred Hospital (Melbourne) from 2017 to 2019. Our primary outcome was daily ECMO cost, and we hypothesized that cost differences among the hospitals could be explained by the efficiencies and skill mix of involved clinicians and prices paid for personnel, equipment, and consumables. Our results are presented relative to Los Angeles' total personnel cost per VV ECMO patient day, indexed at 100. Los Angeles' total indexed daily cost of care was 147 (personnel: 100, durables: 5, and disposables: 42). Paris' total cost was 39 (26% of Los Angeles) (personnel: 12, durables: 1, and disposables: 26). Melbourne's total cost was 53 (36% of Los Angeles) (personnel: 32, durables: 2, and disposables: 19) (rounded). The higher personnel prices at Los Angeles explained only 26% of its much higher personnel costs than Paris, and 21% relative to Melbourne. Los Angeles' higher staffing levels accounted for 49% (36%), and its costlier mix of personnel accounted for 12% (10%) of its higher personnel costs relative to Paris (Melbourne). Unadjusted discharge rates for ECMO patients were 46% in Los Angeles (46%), 56% in Paris, and 52% in Melbourne. We found that personnel salaries explained only 30% of the higher personnel costs at 1 Los Angeles hospital. Most of the cost differential was caused by personnel staffing intensity and mix. This study demonstrates how TDABC may be used in ICU administration to quantify the savings that 1 US hospital could achieve by delivering the same quality of care with fewer and less-costly mix of clinicians compared to a French and Australian site. Narrative reviews contextualized how the care models evolved at each site and helped identify potential barriers to change.